2018
DOI: 10.1136/bmjopen-2017-018320
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive design clinical trials: a review of the literature and ClinicalTrials.gov

Abstract: ObjectivesThis review investigates characteristics of implemented adaptive design clinical trials and provides examples of regulatory experience with such trials.DesignReview of adaptive design clinical trials in EMBASE, PubMed, Cochrane Registry of Controlled Clinical Trials, Web of Science and ClinicalTrials.gov. Phase I and seamless Phase I/II trials were excluded. Variables extracted from trials included basic study characteristics, adaptive design features, size and use of independent data monitoring comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
136
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(152 citation statements)
references
References 35 publications
7
136
2
2
Order By: Relevance
“…The review of adaptive designs by Bothwell et al . () had similar results to those in Hatfield et al . (), except that biomarker adaptive designs (where design modifications are based on treatment effect estimates in groups defined by biomarkers such as baseline disease severity or a genetic marker) were added to the list of most common adaptations.…”
Section: Adaptive Designs In Clinical Trialssupporting
confidence: 88%
See 2 more Smart Citations
“…The review of adaptive designs by Bothwell et al . () had similar results to those in Hatfield et al . (), except that biomarker adaptive designs (where design modifications are based on treatment effect estimates in groups defined by biomarkers such as baseline disease severity or a genetic marker) were added to the list of most common adaptations.…”
Section: Adaptive Designs In Clinical Trialssupporting
confidence: 88%
“…Mistry et al (2017), who reviewed the use of adaptive designs in oncology trials, found that group sequential designs were the most common type of adaptation. The review of adaptive designs by Bothwell et al (2018) had similar results to those in Hatfield et al (2016), except that biomarker adaptive designs (where design modifications are based on treatment effect estimates in groups defined by biomarkers such as baseline disease severity or a genetic marker) were added to the list of most common adaptations. These reviews are consistent with the earlier review by Morgan et al (2014).…”
Section: Types Of Adaptation In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift is driven by the promise of adaptive trial techniques 'to fix experiments before they fail' and to evaluate the clinical potential of candidate treatments faster, which is seen as an opportunity to save costs, time and to recruit fewer patients (Montgomery, 2017, p. 248). For these reasons, the pharmaceutical industry has increasingly adopted adaptive trials (Bothwell et al, 2018). The US Food and Drug Administration (FDA) and the European Medicine Agency (EMA) have recently released guidance documents on adaptive trial designs (FDA, 2016(FDA, , 2018a(FDA, , 2018bEMA, 2017).…”
Section: The Use Of Adaptive Clinical Trial Designsmentioning
confidence: 99%
“…The US Food and Drug Administration (FDA) and the European Medicine Agency (EMA) have recently released guidance documents on adaptive trial designs (FDA, 2016(FDA, , 2018a(FDA, , 2018bEMA, 2017). These documents have enabled drug application sponsors to use adaptive trials for licensing procedures (Bothwell et al, 2018).…”
Section: The Use Of Adaptive Clinical Trial Designsmentioning
confidence: 99%